Early Pregnancy Blood Pressure Patterns Identify Risk of Hypertensive Disorders of Pregnancy Among Racial and Ethnic Groups. Issue 3 (29th December 2021) - Gunderson, Erica P.; Greenberg, Mara; Nguyen-Huynh, Mai N.; Tierney, Cassidy; Roberts, James M.; Go, Alan S.; Tao, Wei; Alexeeff, Stacey E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Hypertensive disorders of pregnancy are a leading cause of severe maternal morbidity and mortality and confer 4-fold higher perinatal mortality in Black women. Early pregnancy blood pressure patterns may differentiate risk of hypertensive disorders of pregnancy. Methods: This study identified distinct blood pressure trajectories from 0 to 20 weeks' gestation to evaluate subsequent pregnancy-related hypertension in a retrospective cohort of 174 925 women with no prior hypertension or history of preeclampsia, prenatal care entry ≤14 weeks, and a stillborn or live singleton birth delivered at Kaiser Permanente Northern California hospitals in 2009 to 2019. We used electronic health records to obtain clinical outcomes, covariables, and longitudinal outpatient blood pressure measurements ≤20 weeks' gestation (mean 4.1 measurements). Latent class trajectory modeling identified 6 blood pressure groups: ultra-low-declining(referent), low-declining, moderate-fast-decline, low-increasing, moderate-stable, and elevated-stable. Multivariable logistic regression evaluated trajectory group-associations with the odds of preeclampsia/eclampsia and gestational hypertension‚ and effect modification by race-ethnicity and prepregnancy body size. Results: Compared with ultra-low-declining, adjusted odds ratios (95% confidence intervals [CIs]) for low-increasing, moderate-stable, and elevated-stable groups were 3.25 (2.7–3.9), 5.3 (4.5–6.3), and 9.2 (7.7–11.1) for preeclampsia/eclampsia‚ and 6.4 (4.9–8.3), 13.6 (10.5–17.7), and 30.2 (23.2–39.4) for gestational hypertension. Race/ethnicity, and prepregnancy obesity modified the trajectory-group associations with preeclampsia/eclampsia (interaction P <0.01), with highest risks for Black, then Hispanic and Asian women for all blood pressure trajectories, and with increasing obesity class. Conclusions: Early pregnancy blood pressure patterns revealed racial and ethnic differences in associations with preeclampsia/eclampsia risk within equivalent levels and patterns. These blood pressure patterns may improve individual risk stratification permitting targeted surveillance and early mitigation strategies.